2013
DOI: 10.2224/sbp.2013.41.9.1469
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Chinese Managerial Competencies from Different Perspectives

Abstract: In this study we investigated assessments of managerial competency in the context of Chinese local government public officials. Based on data collected from a 2008 survey conducted in China's Jiangsu Province and drawing on the competing values framework developed by Rohrbaugh (1981, 1983), we examined discrepancies in the assessment of managerial competencies through the supervisors' self-assessments of their own competencies, subordinates' self-assessments of their own competencies, supervisors assessments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…Other factors may include amount of rater training [44], purpose of rating [45], and motivation of the rater [46]. Also, the significant difference seen in the evaluations concurred with the study of Shang and Yu [47] on the managerial competencies based on self (manager) and subordinate-evaluation. Subordinates' lower rating may be a result of varied perceptions of the role requirements of the managers within the group or organization [43].…”
Section: Key Resultssupporting
confidence: 66%
“…Other factors may include amount of rater training [44], purpose of rating [45], and motivation of the rater [46]. Also, the significant difference seen in the evaluations concurred with the study of Shang and Yu [47] on the managerial competencies based on self (manager) and subordinate-evaluation. Subordinates' lower rating may be a result of varied perceptions of the role requirements of the managers within the group or organization [43].…”
Section: Key Resultssupporting
confidence: 66%
“…The most prior POM competency in terms of PESP has been found to be the 'management skill (B2)' (0.151). 'Management skill' competency has been discussed in many competency studies (Ahn & McLean, 2008;Fang et al, 2010;Shang & Yu, 2013;Thai, 2012). Fang et al (2010), found the 'management skill' as fourth prior competency in their study in relation to the healthcare managers.…”
Section: Source: Authorsmentioning
confidence: 98%
“…The age groups divided in this paper are based on the age at which the applicants started a project. For applicants who have run multiple projects (Shang & Yu, 2013;Shang, Jin & Liu, 2016), we use person-time method to classify them into the age group that corresponds to the project.…”
Section: The Factors Influencing Outputmentioning
confidence: 99%